(NkOLLEKCIONER (B:s (NROMAN (B/s - (NfAULZ(B, (NdVON(B,s; (NbESSMERTNA(B, (Ni(B.,s ((NmOSKWA (B:s (N|KSMOs (NsANKT(B-(NpETERBURG (B:s (NdOMINO(B,s, 2011)
(NdEB@TNYJ ROMAN ANGLIJSKOGO PISATELQ dV(B. (NfAULZAs
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NaNGL)QÆJSXKA LÆTERATURAs)E; (NKOLEKC)QÆONERs)E